Aligned cuboid iron nanoparticles by epitaxial electrodeposition. Issue 16 (11th April 2017) - Leistner, Karin; Yang, Mingze; Damm, Christine; Oswald, Steffen; Petr, Andreas; Kataev, Vladislav; Nielsch, Kornelius; Kavanagh, Karen L.
Abstract : Aligned cuboid iron nanoparticles with magnetic anisotropy and long term stability are achieved by epitaxial room-temperature electrodeposition. Abstract : Aligned, individual iron square cuboid nanoparticles have been achieved by taking advantage of epitaxial, three-dimensional-island growth on GaAs(001) during electrodeposition at low deposition rates. The nanoparticles exhibit lateral dimensions between 10 and 80 nm and heights below 40 nm. Surface {100} facets predominate with a thin crystalline oxide shell that protects the nanoparticles during prolonged storage in air. The single crystallinity of the iron in combination with structural alignment leads to an in-plane magnetic anisotropy. These immobilized, oriented, and stable nanoparticles are promising for applications in nanoelectronic, sensor, and data storage technologies, as well as for the detailed analysis of the effect of shape and size on magnetism at the nanoscale.